Contribution à la connaissance du paléolithique dans les environs de Chartres : étude techno-typologique des collections de la commune de Bas-de-Luisant (Eure-et-Loir) - Hélène Djema (Revue Archéologique du Centre de la France)
The prehistoric site of Bas-de-Luisant in Eure-et-Loir was discovered at the end of the 19th century. For several decades it has been the subject of occasional visits of distinguished prehistorians and amateurs who collected an interesting lithic collection. Kept in Chartres Museum of Natural History reserves, this collection has not yet been studied. Although, it is one of the rare Palaeolithic sites discovered in primary position in this sector. The techno-typological study presented in this paper intends to document the technical process and tools of the collection. Two main cultures have been identified. The majority of the lithic industry is Mousterian: Levallois production (points, flakes, blades), bifacial MTA. The rest of the industry is assigned to the ancient Palaeolithic, in a broad sense. It is characterized by a wide bifacial spectrum clearly rolled during fluvial transport. In terms of techno-economic organization, the selective collection limits significantly our interpretations. However, the good conservation of the Mousterian material suggests that a complete typo-technological and techno-economic study could be considered, provided that a modern excavation is possible. This study is a first contribution to the understanding of the Palaeolithic human occupation in this area.